Caracterização de retrotransposons LTR e variabilidade genética em populações de Sclerotinia sclerotiorum do Estado de Minas Gerais - Goldfarb, Míriam (Universidade Federal de Viçosa, 2014)
Sclerotinia sclerotiorum é o agente causal do mofo-branco e pode causar doenças em mais de 200 gêneros de plantas, abrangendo 408 espécies hospedeiras. Os elementos transponíveis encontrados no genoma de diversos fungos, podem ser utilizados como marcadores para traçar o perfil genético de populações de fungos fitopatogênicos. Os objetivos deste trabalho foram: i) identificar e classificar retrotransposons no genoma de S. sclerotiorum e utilizá-los como marcadores moleculares por meio da técnica IRAP (Inter Retrotransposon Amplified Polymorphism) e ii) estimar a variabilidade genética de S. sclerotiorum de diferentes regiões do estado de Minas Gerais. Foram identificados no banco genômico de Sclerotinia sclerotiorum dois retrotransposons denominados de Copia-LTR_SS e Gypsy-LTR_SS. Esses elementos pertencem às superfamílias Copia e Gypsy, respectivamente. O retroelemento Copia- LTR_SS possui sequências de 5.344 pb, uma ORF (sequência de leitura aberta) que codifica as proteínas gag e a presença de todas as proteínas da região pol, incluindo as enzimas que integram o transposon no genoma. O retroelemento Gypsy-LTR_SS possui sequências de 6.469 pb, sequências que codificam a proteína gag e a região pol com apenas sequências que codificam as enzimas transcriptase reversa e RNAse H. Os dois elementos possuem regiões PPT (Polypurine Tract) e PBS (Primer Binding Site). Um grande número de LTRs-Solo e elementos TRIMs foram identificados como também a presença de mecanismo de silenciamento do tipo RIP (Repeat-Induced Point Mutation) capaz de inativar os transposons por meio mutações pontuais. A presença de LTR- Solo e TRIM (terminal-repeat retrotransposon in miniature) em S. sclerotiorum evidencia a ocorrência de recombinações no genoma desta espécie de fungo e sugere uma restruturação do mesmo mediado por elementos transponíveis. O marcador molecular IRAP foi eficiente para identificar marcas polimórficas no genoma de S. sclerotiorum, permitindo assim o estudo de variabilidade genética neste fungo. Foi estimada a variabilidade genética em populações de S. sclerotiorum do estado de Minas Gerais, compreendendo 98 isolados procedentes de quatro regiões geográficas (Zona da Mata, Noroeste, Sul e Triângulo Mineiro). Alta diversidade genética foi observada em todas as populações avaliadas, sendo os valores de diversidade gênica de Nei e dos índices de Shannon estimados em 0,17 a 0,35 (diversidade gênica de Nei) e 0,27 a 0,52 (Índice de Shannon). A análise da AMOVA resultou em altos valores de variação gênica dentro das subpopulações analisadas sendo de 99,74% para as subpopulações da Zona da Mata e de 100% para as do Noroeste. Os baixos valores de Fst para Zona da Mata (0,00262) e Noroeste (-0,02150) indicam que nestas duas populações suas respectivas subpopulações não estão geneticamente estruturadas quanto à região geográfica. O marcador molecular IRAP foi eficiente para identificar marcas polimórficas no genoma de S. sclerotiorum. O presente trabalho é o primeiro estudo relatado sobre análise de diversidade S. sclerotiorum com base em transposons. Os dados obtidos poderão contribuir para a implementação de estratégias de controle e manejo do mofo-branco bem como para elaboração de programas de melhoramento genético do feijoeiro.

Sclerotinia sclerotiorum is the causal pathogenic agent of the white mold and it is able to cause diseases in more than 200 different species of plants, including 408 host species. The transposable elements were detected in the genome of various species of fungus. These elements can also be used as markers for the characterisation of the genetic profile and the populations of the phytopathogenic fungi. The topic and aim of this research is: (i) to identify and classify the retrotransposons in the genome of S. sclerotiorum and the application of the same to serve as a molecular marker using the IRAP (Inter Retrotransposon Amplified Polymorphism) technique and ii) to estimate the genetic variability of S. sclerotiorum in different regions in the State of Minas Gerais. In the genomic bank of Sclerotinia sclerotiorum two different kind of retrotransposons called Copy LTR _ SS and Gypsy-LTR_SS were identified. Each of these elements belongs in the superfamilies named of the Copy and Gypsy. The Copy- LTR _ SS retroelement has the sequences with the value of 5.344 pb and an ORF (Open Reading Frame), that encodes the Gag proteins and the presence of all the proteins from the pol region, also including the enzymes which contain the transposon inside the genome. The Gypsy- LTR_ SS retroelement has the sequences with the value of 6.469 pb. These sequences encode the gag protein and the pol region, which exclusively consist of sequences that encode the reverse transcriptase and RNase H enzymes. The two elements, which were identified, consist of the PPT region (Polypurine Tract) and the PBS region (Primer Binding Site). Furthermore a large number of Solo LTRs and TRIMs elements were identified and the presence of the mechanism of inactivation of the transposon RIP (Repeat-Induced Point Mutation) were proved. This mechanism is able to inactivate the transposons by selective mutations. LTR-solo and TRIM (terminal-repeat retrotransposon in miniature) were found in S. sclerotiorum, which indicate the presence of recombinations in the genome of this specie. This is a sign of a restructuration of the genome that are mediated through the transposable elements. The molecular marker IRAP was efficiently used to identify the polymorphic marks in the genome of S. sclerotiorum. Thus it will be possible to enable the study of the genetic variability in this sort of fungus. An estimation was performed to confirm the genetic variability of the populations of S. sclerotiorum in the State of Minas Gerais. Therefore 98 isolates from four different regions in the State of Minas Gerais were needed for the experiment (Zona da Mata, Northwest, South and Triângulo Mineiro). A high genetic diversity was observed in all the evaluated populations, also confirmed by the high values for the genetic diversity, which were found by Nei and Shannon. The estimated values were between 0,17 up to 0,35 (genetic diversity) and between 0,27 up to 0,52 (Index of Shannon). Moreover the analysis of the AMOVA-research provided and cofirmed the high values for the genetic variation, 99,74% of variation within the subpopulations in the Zona da Mata, and 100% of variation within the subpopulations in the Northwest. Considering the geographic region, the low values of Fst for the Zona da Mata (0,00262) and Northwest (-0,02150) suggest that these two populations and their respective subpopulations were not genetically structured. The molecular marker IRAP was efficiently used to identify the polymorphic marks in the genome of S. sclerotiorum. The present work is the first reported study, which is concerned with the analysis of the diversity in S. sclerotiorum based on transposons. The obtained data could be used to contribute the implementation of strategies to control and handle the white mold, as well as it could be useful for the preparation of programs for the genetic improvement of beans.
Characterization of LTR retrotransposons and genetic variability in populations of Sclerotinia sclerotiorum of the state of Minas Gerais
Keywords: Sclerotinia sclerotiorum; Mofo-branco; Genoma; Diversidade genética; Fungos fitopatogênicos; Sclerotinia sclerotiorum; White mold; genome; Genetic diversity; Pathogenic fungi; CNPQ::CIENCIAS BIOLOGICAS::BIOLOGIA GERAL